Comparison of measurement properties of three shortened versions of the Balance Evaluation Systems Test (BESTest) in people with subacute stroke - WINAIRUK, Thitimard (J Rehabil Med, 2019)
OBJECTIVES: To examine the reliability, validity and responsiveness of 3 different short versions of the BESTest (S-BESTest, Brief-BESTest and Mini-BESTest) in patients with subacute stroke. DESIGN: A prospective cohort study. PARTICIPANTS: Patients with subacute stroke. METHODS: Patients were assessed using the full BESTest and scores of 3 short-form BESTests were later extracted. The intra-rater and inter-rater reliability (N=12) were gathered from 5 raters. Concurrent validity was assessed with the Berg Balance Scale (BBS). Floor/ceiling effect, internal responsiveness and external responsiveness with the BBS (N=70) were assessed at baseline, 2 weeks and 4 weeks post-rehabilitation. RESULTS AND CONCLUSION: All short-form BESTests demonstrated excellent intra-rater and inter-rater reliability (ICC=0.95–0.99) and excellent concurrent validity (r=0.93–0.96). Unlike the Brief-BESTest and Mini-BESTest, the S-BESTest and BESTest had no significant floor/ceiling effects (<20%). The SRM of all 4 BESTest versions were large, ranging between 1.19 to 1.57, indicating sufficient internal responsiveness. The AUC of the S-BESTest and BESTest were significantly higher than the Brief-BESTest and Mini-BESTest, reflecting better accuracy of the S-BESTest and BESTest in identifying patients with subacute stroke who had balance improvement using the MCID of 6 and 16 points, respectively. These findings suggest that the S-BESTest is a short-form BESTest that is appropriate for assessing balance impairments in patients with subacute stroke.